1975
DOI: 10.1073/pnas.72.8.2925
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-dependent hydrolysis of cholesteryl esters contained in plasma low density lipoprotein.

Abstract: Selective radioactive labeling of the cholesteryl esters contained within human plasma low density lipoprotein has allowed the study of the metabolism of these molecules in monolayers and extracts of cultured human fibroblasts. In monolayers of normal cells, binding of low density lipoprotein to its cell surface rece tor was followed by rapid hydrolysis of the [3H] METHODS Cells. Cultured fibroblasts were derived from skin biopsies obtained from either normal subjects or patients with the receptor-negative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(66 citation statements)
references
References 14 publications
(10 reference statements)
2
64
0
Order By: Relevance
“…The HDL 3 preparation used in this study contained 0-1.5% of preb-migrating species. LDL was acetylated in the presence of acetic anhydride (32), and the acetyl-LDL was radiolabeled by treatment with [1,2-3 H]cholesteryl oleate (Amersham Biosciences, Piscataway, NJ) dissolved in dimethyl sulfoxide (33). The specific activity of the [ 3 H]CE-acetyl-LDL preparation was 46 dpm/ng protein.…”
Section: Isolation and Radiolabeling Of Lipoproteinsmentioning
confidence: 99%
“…The HDL 3 preparation used in this study contained 0-1.5% of preb-migrating species. LDL was acetylated in the presence of acetic anhydride (32), and the acetyl-LDL was radiolabeled by treatment with [1,2-3 H]cholesteryl oleate (Amersham Biosciences, Piscataway, NJ) dissolved in dimethyl sulfoxide (33). The specific activity of the [ 3 H]CE-acetyl-LDL preparation was 46 dpm/ng protein.…”
Section: Isolation and Radiolabeling Of Lipoproteinsmentioning
confidence: 99%
“…The upper layer was further subjected to zonal ultracentrifugation, and the 0-VLDL was separated. LDL was acetylated by the method of Basu et al 18 Acetylated LDL was iodinated with sodium by using dimethyl sulfoxide and the method of Brown et al 18 The specific activity of 12S l-acetylated LDL was 69 cpm/ ng protein, and the percent lipid labeling was less than 4.5%. The specific activities of 3 H-cholesteryi linoleatelabeled acetylated LDL fH-CE-acetylated LDL) and 3 H-cholestery1 linoleate-labeled 0-VLDL fH-CE-jS-VLDL) were 26.2 and 21.3 dpm/ng total cholesterol, respectively.…”
Section: Preparation Of Upoprotelnsmentioning
confidence: 99%
“…Then, the degradation and cellular association of 12S l-acetyiated LDL were determined by the method of Goldstein and Brown. 18 Briefly, the nontodide radioactivity in the trichloroacetJc acid-soluble fraction of the medium was counted to determine the degradation of 126 l-acetylated LDL. Additional incubation of 125 l-acetylated LDL without cells was used to correct for non-cell-mediated degradation, 20 which was less than 10% of the total degradation.…”
Section: Degradation Cellular Association and Binding Of Ttb L-acetmentioning
confidence: 99%
“…Ultrastructural observations have shown that the lipids accumulate in cells in two distinct states (6,9,23,24), either as lipid droplets surrounded by a limiting membrane in the phagolysosomesor as droplets without a limiting membranein the cytoplasm. Cholesteryl ester-lipid droplets are originally derived from lipoproteins in the blood stream (2,3). Arterial cells take up lipoproteins by endocytosis, hydrolyze the cholesteryl esters with lysosomal acid cholesteryl esterase, and re-esterify the free cholesterol with microsomal acyl-CoA: cholesterol acyltransferase (ACAT) (4, 5, 10).…”
mentioning
confidence: 99%